Harnessing the educational value of folktales in teaching moral education for primary school students - Thu, Hang Nguyen Thi; Bich, Ngoc Nguyen Thi; Thu, Trang Nguyen Thi (Edelweiss Applied Science and Technology, 2025)
This study investigates whether a structured folktale-based pedagogical approach can strengthen moral education for primary students under typical classroom conditions. We developed a four-step sequence: selection of locally relevant folktales aligned with lesson standards, storytelling, guided analysis of characters’ actions and consequences, and creative moral problem-solving with reflection. It was implemented in Grade-5 classrooms using a quasi-experimental pre–post design (experimental n = 25; control n = 25). Moral development was assessed on five criteria: recognition of right and wrong, moral analysis and evaluation, behavior in new situations, attitudes toward moral behavior, and real-life application, using rubrics, classroom observations, and student outputs. Implementation was feasible within ordinary lesson time; the experimental class showed marked pre–post gains across all criteria, while the control class changed minimally. Teachers reported high relevance, clarity, and usability for routine instruction. Thus, folktale-based instruction effectively translates abstract moral norms into concrete, emotionally engaging experiences that enhance students’ moral cognition, attitudes, and behavior. The study contributes a classroom-ready pedagogical model with replicable lesson steps and assessment rubrics that teachers can adapt to local narratives within competency- and value-based curricula.